Potential Complications of Percutaneous Vertebroplasty Combined with Interstitial Implantation of 125I Seeds for Metastatic Spinal Tumors: A Case Report and Literary Review - Lunli Xie; Zhenlin Yan; Jun Zhu; Xudong Chen; Changyuan Yang; Xing Su; Keqin Quan; Dan Pu (Case Reports in Orthopedics)
Percutaneous vertebroplasty is often used to acquire the stability of the spine and relieve the pain caused by osteoporotic vertebral compressive fracture (OVCF). 125I seeds have been used for application of local therapy for tumors. A combined treatment was reported in previous literatures. Thus, this case report is aimed at reporting a patient with an occurrence of delayed radioactive myelopathy, who accepted percutaneous vertebroplasty combined with interstitial implantation of 125I seeds for metastatic spinal tumors, and at reviewing the published literatures.